Improving protection of victims’ rights in Latvia – access to legal aid and mediation as a toll to settle the conflict - Sile, S.; Ziedina, D. (My University, 2014)
The state compensation and legal aid to victims of criminal offences are only two small elements of what such system should entail. The victim compensation system as described in the Criminal Procedure Law and in the Criminal Law is only a part of the compensation mechanism and support provided to certain groups of victims does not mean that Latvia has a victim support system. Similarly, financing assigned annually for payment of the state guaranteed compensation from the state budget is not to be considered a victim compensation fund.
Keywords: protection of victims’ rights in Latvia